Analisis Potensi Terjadinya Swabakar Batubara Dengan Penambahan Chemical Pada Stockrom Jetty di PT. Bhumi Sriwijaya Perdana Coal, Desa Bero Jaya Timur, Kecamatan Tungkal Jaya, Kabupaten Musi Banyuasin, Sumatera Selatan - Muhammd Thoriq; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2022)
PT.Coal (Bhumi Sriwijaya Perdana)BSPC) is a coal mining company in the East Sumatra Province's East Bero Jaya Village, Tungkal Jaya District, Musi Banyuasin Regency.PT.An open pit mining system is put in place by BSPC.The grade of the coal in PT.The total moisture content of Bhumi Sriwijaya Perdana Coal is extremely high, at 45 percent.Because coal has a high total moisture content, PT.In order to maintain total moisture, BSPC innovates by utilizing chemicals that contain surfactant polymers.Quantitative research, also known as experimental research, is the research method used.The coal parameters' values changed in the research that was done.Ten tons of coal and one liter of chemicals were used in the tests to compare how well Coalguard (P2), Supercoat (P3), and not using water (P1) performed.The pile's temperature dropped from 52.80°C on March 8, 2022, to 40.30°C on March 27, 2022, if Coalguard 575 was applied, compared to the initial temperature at which Supercoat was applied. The pile received G-Clean Supercoat and Coal Guard, respectively.It is known that the addition of a chemical (G-Clean Supercoat, Coal Guard 575) reduces the temperature at which swabaka occurs by an average of 54.77 degrees Celsius, 44.02 degrees Celsius, and 44.79 degrees Celsius for the P1, P2, and P3 piles, respectively.The use of polymer in coal has the potential to lower the total moisture value, as demonstrated by the effect that the polymer has on the parameters of the coal following its application, particularly the value of the water content.